Immunohistochemical Investigation of Autonomic and Sensory Innervation of Anterior Vaginal Wall Female Periurethral Tissue: A Study of the Surgical Field of Mid-Urethral Sling Surgery Using Cadaveric Simulation. Issue 7 (24th June 2021) - Giovannetti, Olivia; Tomalty, Diane; Gaudet, Dionne; Clohosey, Diandra; Forster, Autumn; Monaghan, Madeline; Harvey, Marie Andrée; Johnston, Shawna; Komisaruk, Barry; Goldstein, Sue; Hannan, Johanna; Goldstein, Irwin; et al.
ABSTRACT: Background: Female sexual dysfunction, including female orgasm disorder, has been reported following mid-urethral sling (MUS) surgery to treat bothersome stress urinary incontinence. Anterior vaginal wall-female periurethral tissue (AVW-FPT) likely contains autonomic and sensory innervation involved in the female sexual response, and injury to these nerves may result from MUS implantation. Aim: To characterize, using fresh cadaveric tissue, autonomic and sensory nerves in AVW- FPT using immunohistochemistry (IHC), and to assess their proximity to an implanted MUS. Methods: AVW-FPT was excised following careful dissection from four fresh cadavers. Prior to dissection, one cadaver underwent simulation of the MUS procedure by a urogynegologist, using a fascial sling. All samples were paraffin embedded, sectioned, and stained with hematoxylin. Serial sectioning and IHC were performed to identify nerves. IHC markers were used to characterize the sensory and autonomic innervation. Outcomes: IHC localization of autonomic and sensory nerve markers consistent with neural tissue within the region of MUS implantation. RESULTS: IHC of AVW-FPT using protein gene product 9.5 (PGP9.5), a general nerve stain, revealed innervation throughout the region targeted by the MUS implantation. More specifically, immunoreactivity for both autonomic (tyrosine hydroxylase, TH) and sensory (Nav 1.8 and S100ß) nerves were found in close proximity (<1 mm) to the implanted MUS. In addition, a subset of S100ß positive nerves also showed immunoreactivity for calcitonin gene-related peptide (CGRP). Combining the IHC findings with the surgical simulation of the MUS implantation revealed the potential for damage to both autonomic and sensory nerves as a direct result of the MUS procedure. Clinical Translation: The identified autonomic and sensory nerves of the AVW-FPT may contribute to the female sexual response, and yet are potentially negatively impacted by MUS procedures. Given that surgeries performed on male genital tissue, including the prostate, may cause sexual dysfunction secondary to nerve damage, and that urologists routinely provide informed consent regarding this possibility, urogynaecologists are encouraged to obtain appropriate informed consent from prospective patients undergoing the MUS procedure. Strengths & Limitations: This is the first study to characterize the sensory and autonomic innervation within the surgical field of MUS implantation and demonstrate its relationship to an implanted MUS. The small sample size is a limitation of this study. CONCLUSION: The present study provides evidence of potential injury to autonomic and sensory innervation of AVW-FPT as a consequence of MUS implantation, which may help explain the underlying mechanisms involved in the reported post-operative female sexual dysfunction in some women.